2023
DOI: 10.1002/nafm.10936
|View full text |Cite
|
Sign up to set email alerts
|

Pacific Lamprey and Western River Lamprey marine ecology: Insight from new ocean collections

Abstract: Little is known about the marine ecology of anadromous Pacific Lamprey Entosphenus tridentatus and Western River Lamprey Lampetra ayresii. This information is needed to determine how marine life regulates adult abundances and identify management actions that may benefit declining populations. To address this deficit, we compiled historic data, collected lamprey from marine stock assessment surveys and commercial fisheries, and documented fish with Pacific Lamprey wounds. Pacific Lamprey were most commonly caug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…include the Western River Lamprey L. ayresii and Western Brook Lamprey L. richardsoni, which are not genetically distinct (Carim et al 2023), and the Pacific Brook Lamprey L. pacifica, which appears to be currently limited to the Willamette River basin (Reid et al 2011;Carim et al 2023) and thus was outside our study area. Like Pacific Lamprey, Western River Lamprey are anadromous (Weitkamp et al 2015(Weitkamp et al , 2023. Tissue was sampled from a subset of larvae for future genetic confirmation of morphological identification.…”
Section: Field Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…include the Western River Lamprey L. ayresii and Western Brook Lamprey L. richardsoni, which are not genetically distinct (Carim et al 2023), and the Pacific Brook Lamprey L. pacifica, which appears to be currently limited to the Willamette River basin (Reid et al 2011;Carim et al 2023) and thus was outside our study area. Like Pacific Lamprey, Western River Lamprey are anadromous (Weitkamp et al 2015(Weitkamp et al , 2023. Tissue was sampled from a subset of larvae for future genetic confirmation of morphological identification.…”
Section: Field Samplingmentioning
confidence: 99%
“…Anadromous lampreys transform from larvae into ectoparasitic juveniles and then migrate to the ocean to feed on host fishes and whales (Dawson et al 2015;Clemens et al 2019). Although the duration of ocean residence is not well known and may vary among lamprey species and individuals, it is thought that Pacific Lamprey reside in the ocean for several years (Beamish 1980;Hess et al 2022;Weitkamp et al 2023, this special section). Resident nonparasitic lampreys transform directly from larvae into adults.…”
Section: Introductionmentioning
confidence: 99%
“…Freshwater juveniles that were casualties from a screw trap on a tributary (Ahtanum Creek) of the Yakama River were also provided by the YNF. Marine juveniles collected as bycatch from the National Oceanic and Atmospheric Administration's (NOAA) At-Sea Hake Observer Program in the summers of 2017 and 2018 were provided by the Northwest Fisheries Science Center (Weitkamp et al 2023, this special section). Adult samples, the majority of which were collected during the 2016 tribal harvest at Willamette Falls, Oregon, were provided by CRITFC.…”
Section: Samplesmentioning
confidence: 99%
“…Medland and Beamish (1991) found that temperature affected the growth of larval Sea Lamprey statoliths, which stopped growing at or below 8°C. Pacific Lamprey are known to parasitize Pacific Hake Merluccius productus and other species with relatively deep depth distributions (Weitkamp et al 2023), which could keep them in relatively cool waters, although some variation in thermal exposure would be expected. The sole use of hatchery larvae in this study could have contributed to the strong positive relationship between statolith and body size, as studies of hatchery salmon otoliths indicate that artificial rearing results in wider and more uniform growth rings (Zhang et al 1995;Barnett-Johnson et al 2007;Claiborne et al 2014).…”
Section: Modelmentioning
confidence: 99%
“…Results from Blanchard et al (2023, this special section) and Liedtke et al (2023, this special section) inform the distribution of larval lampreys in freshwater habitats from small (e.g., sediment distribution) to large scales (basin-wide distribution) and highlight effects of stream management decisions on larval lamprey populations. Weitkamp et al (2023, this special section) is the most comprehensive evaluation to date on the marine ecology of Pacific Lamprey and Western River Lamprey. This research adds much to the little currently known about marine biology of anadromous lampreys of conservation concern (Clemens et al 2019;Shink et al 2019;Quintella et al 2021).…”
Section: Life History and Population Dynamicsmentioning
confidence: 99%